2017
DOI: 10.11648/j.cajph.20170303.12
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Age Related Disparity in Oral Health Knowledge, Attitude and Practice Among Elderly Pensioners in Port Harcourt, Rivers State

Abstract: There is an increased interest in looking at age and gender differences in health and disease, including oral health.The objective of this study was to determine the influence of age and gender on oral health knowledge, attitude and practice of pensioners in Port Harcourt, Rivers State, Nigeria. The research was analytic descriptive survey in design. A total of 543 old people were selected by systematic random sampling. Data was collected with a self-developed Oral Health Assessment Questionnaire (OHAQ) design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
3
1
2
Order By: Relevance
“…Therefore, better attitudes of oral care in elderly people aged 71 to 75 may be due to their adjustment after retirement. Although age was not found as a factor associated with practices of oral care, another study found that increased age was, in fact, correlated with significantly lower oral health practices [31].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, better attitudes of oral care in elderly people aged 71 to 75 may be due to their adjustment after retirement. Although age was not found as a factor associated with practices of oral care, another study found that increased age was, in fact, correlated with significantly lower oral health practices [31].…”
Section: Discussionmentioning
confidence: 87%
“…Maintaining better oral health with adequate moisture in the mouth, such as regular drinking water or rinsing the mouth, is fundamental knowledge [16,18]. However, such basic knowledge for oral health, including frequency of tooth-brushing and regular dental visits, worsens among old age groups [31,32]. In the Chinese population, elderly people were found to have poor dental health habits and attitudes, including the lack of using dental floss or attending regular dental checkups [33].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of edentulism was higher in participants with a history of smoking, brushing fewer than twice a day, and not taking yearly oral examinations 45 , 46 . These oral health behaviors showed different patterns depending on the sexual difference, and females are known to visit the dentist more frequently, perform better oral care 47 , and have better knowledge, attitude, and behavior about oral health than males 48 , 49 . The elderly female showed about a 10% higher rate of brushing their teeth twice or more a day than males in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sejalan dengan penelitian Bashiru BO menunjukkan hasil terdapat hubungan yang signifikan antara pengetahuan dengan usia. 16 Beberapa faktor yang memengaruhi pengetahuan salah satunya adalah usia dan pendidikan , ataupun disebabkan karena anak usia 15 tahun jauh lebih banyak menerima informasi sehingga pemahamannya jauh lebih baik. Menurut Huclok semakin cukup umur, seseorang akan lebih matang dalam berpikir dan bekerja.…”
Section: Hasilunclassified
“…Sejalan dengan penelitian Bashiru BO menunjukkan terdapat hubungan yang signifikan antara sikap dengan jenis kelamin. 16 Sejalan dengan teori Lewin (1970) dan Green (1991) menunjukkan bahwa usia dan jenis kelamin dapat memengaruhi terbentuknya sikap seseorang. Menurut Hadi (2008), perkembangan kognitif, penalaran moral, perkembangan sosial berhubungan pertambahan usia.…”
Section: Hasilunclassified